2014
DOI: 10.5732/cjc.014.10031
|View full text |Cite
|
Sign up to set email alerts
|

The Good Pain Management (GPM) Ward Program in China and its impact on Chinese cancer patients: the SYSUCC experience

Abstract: To improve cancer pain management, the Medical Oncology Department of Sun Yat-sen University Cancer Center (SYSUCC) launched the Good Pain Management (GPM) Ward Program, which has been recognized by the Chinese Ministry of Health and promoted throughout the nation. This retrospective case-control study was designed to evaluate the effectiveness of the program. Patients diagnosed with malignant solid tumors with bone metastasis were eligible. Patients who were admitted 6 months before the initiation of the GPM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
22
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 23 publications
4
22
0
Order By: Relevance
“…After pharmacist intervention, the data dropped to 11.79% at the fourth visit, and the mean pain intensity was reduced by 0.70 on a 0-10 scale. These data are consistent with the results of Edwards et al and Yang et al 19,21 The metaanalysis of Edwards et al found that the mean pain intensity in the intervention group was reduced by 0.76 on a 0-10 scale. In the study by Yang et al, 21 the uncontrolled pain rate in the GPM group was significantly lower than that of the control group (13.8% vs. 31.5%, P ¼ 0.001), and the pain score was also reduced by 1.1 to 2.5.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…After pharmacist intervention, the data dropped to 11.79% at the fourth visit, and the mean pain intensity was reduced by 0.70 on a 0-10 scale. These data are consistent with the results of Edwards et al and Yang et al 19,21 The metaanalysis of Edwards et al found that the mean pain intensity in the intervention group was reduced by 0.76 on a 0-10 scale. In the study by Yang et al, 21 the uncontrolled pain rate in the GPM group was significantly lower than that of the control group (13.8% vs. 31.5%, P ¼ 0.001), and the pain score was also reduced by 1.1 to 2.5.…”
Section: Discussionsupporting
confidence: 91%
“…These data are consistent with the results of Edwards et al and Yang et al 19,21 The metaanalysis of Edwards et al found that the mean pain intensity in the intervention group was reduced by 0.76 on a 0-10 scale. In the study by Yang et al, 21 the uncontrolled pain rate in the GPM group was significantly lower than that of the control group (13.8% vs. 31.5%, P ¼ 0.001), and the pain score was also reduced by 1.1 to 2.5. The uncontrolled pain rate was slightly higher than 30%, even without pharmacist involvement, in this study and in the non-GPM group in the study by Yang et al, 21 which was lower than the literature in China, with 41.3%-52.9% of patients not being prescribed adequate analgesics or being satisfied with pain management.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The GPM programme emphasised the control of cancer pain and reasonable application of opioids. Yang et al 24 revealed that the GPM programme could improve the pain management of patients with cancer and provide experience for improving cancer pain management in the future.…”
Section: Discussionmentioning
confidence: 99%